Accidental intoxication with hydrochloric acid and hydrofluoric acid mixture - Anna Smędra-Kaźmirska; Maciej Kędzierski; Maciej Barzdo; Agnieszka P. Jurczyk; Stefan Szram; Jarosław Berent (Archives of Forensic Medicine and Criminology, 2014)
The paper describes a fatal case of accidental ingestion of a mixture of hydrochloric acid and hydrofluoric acid. The man was admitted to hospital, where appropriate treatment, adequate to his condition, was instituted. Numerous ventricular fibrillation episodes, for which the patient was defibrillated repeatedly, were observed during the period of hospitalization. The patient was in a critical condition, with progressive symptoms of hypovolemic shock and multiorgan failure. On the next day after admission, signs of electromechanical dissociation progressing to asystole were noted. The instituted resuscitation procedure proved ineffective and the patient died. Autopsy revealed brownish discoloration of the esophageal, gastric, and small intestinal mucous membranes. Numerous ulcerations without signs of perforation were found both in the esophagus and in the stomach. The mucous membrane of the small intestine demonstrated focal rubefactions, whereas no focal lesions of the large intestinal mucosa were seen. Microscopic investigation of the biopsy specimens collected from the stomach, duodenum and small intestine revealed mucous membrane necrosis foci, reaching the deeper layers of the wall of these organs. The mucous membrane of the large intestine was congested. Bioptates obtained from the lungs indicated the presence of hemorrhagic infarcts and focal extravasations. Poisoning with the aforementioned acids with consequent necrosis of the esophageal, gastric, duodenal and small intestinal walls with hemorrhages to the gastrointestinal tract, as well as extravasations and hemorrhagic infarcts in the lungs was considered to be the cause of death.